2020
DOI: 10.3390/f11020237
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Transpiration to Evapotranspiration Ratio under Wet and Dry Canopy Conditions in a Humid Boreal Forest

Abstract: Humid boreal forests are unique environments characterized by a cold climate, abundant precipitation, and high evapotranspiration. Transpiration ( E T ), as a component of evapotranspiration (E), behaves differently under wet and dry canopy conditions, yet very few studies have focused on the dynamics of transpiration to evapotranspiration ratio ( E T / E ) under transient canopy wetness states. This study presents field measurements of E T / E at the Montmorency Forest, Québec, Canada:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 83 publications
(133 reference statements)
5
17
0
Order By: Relevance
“…(2020a) and Hadiwijaya et al. (2020) and the stable water isotope analyses of this study revealed that sublimation and plant transpiration were negligible in winter and during the snowmelt period, therefore, loss of snow to sublimation was assumed negligible for the calculation of ΔSsnow. To calculate ΔSsnow, d snow was transformed into snow water equivalent according to Sturm et al.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…(2020a) and Hadiwijaya et al. (2020) and the stable water isotope analyses of this study revealed that sublimation and plant transpiration were negligible in winter and during the snowmelt period, therefore, loss of snow to sublimation was assumed negligible for the calculation of ΔSsnow. To calculate ΔSsnow, d snow was transformed into snow water equivalent according to Sturm et al.…”
Section: Methodsmentioning
confidence: 73%
“…The different ET components were not measured separately. However, research by Isabelle et al (2020a) and Hadiwijaya et al (2020) and the stable water isotope analyses of this study revealed that sublimation and plant transpiration were negligible in winter and during the snowmelt period, therefore, loss of snow to sublimation was assumed negligible for the calculation of snow ΔS . To calculate snow ΔS , d snow was transformed into snow water equivalent according to Sturm et al (2010) using the average snow density ( snow  ) observed underneath the flux tower (i.e., 0.335 g/cm 3 ; Parajuli et al (2020a)).…”
Section: Residual Water Budget Approachmentioning
confidence: 71%
“…At a particularly wet site of eastern Canada (annual precipitation 1600 mm), Isabelle et al (2020) reported that annual E appeared to peak at 550 mm, suggesting that this value could represent the balance between high water availability and low atmospheric demand for water vapour associated with frequent rainfall events. At the same site, Hadiwijaya et al (2020) showed that on a seasonal scale, the E T to E ratio did not exceed 0.47 and that the canopy was frequently wet, again suggesting the importance of E C . At drier sites of the boreal forest (annual precipitation between 450 and 670 mm), intercepted rainfall by the canopy ( I c ) was found to account for 9%–55% of the annual precipitation (Grelle et al, 1997; Lankreijer et al, 1999; Morris et al, 2003; Pomeroy et al, 1999), while E C could represent 23%–25% of the total E (Grelle et al, 1997; Pomeroy et al, 1999).…”
Section: Introductionmentioning
confidence: 92%
“…)), and black spruce (Picea mariana (Mill.)) [54]. Due to past logging operations, there are several patches of forest clearings accompanied by spatially varying stand structures ( Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…Due to past logging operations, there are several patches of forest clearings accompanied by spatially varying stand structures ( Figure 1). For detailed descriptions of the study area, please refer to Parajuli et al [51], Isabelle et al [52,55] and Hadiwijaya et al [54]. turbulent and radiative fluxes between the canopy and the atmosphere.…”
Section: Study Areamentioning
confidence: 99%